2016
DOI: 10.1186/s12936-016-1339-x
|View full text |Cite
|
Sign up to set email alerts
|

High efficacy of artemether-lumefantrine and declining efficacy of artesunate + sulfadoxine-pyrimethamine against Plasmodium falciparum in Sudan (2010–2015): evidence from in vivo and molecular marker studies

Abstract: BackgroundThe present paper reports on studies that evaluated artesunate + sulfadoxine-pyrimethamine (AS + SP) which is the first-line drug and artemether-lumefantrine (AL) which is a second-line drug against uncomplicated falciparum malaria in Sudan. This evaluation was performed in twenty studies covering six sentinel sites during five successive annual malaria transmission seasons from 2010 to 2015.MethodsThe standard World Health Organization protocol was used for a follow-up period of 28 days. The frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 43 publications
(54 reference statements)
7
17
0
Order By: Relevance
“…were also included in this review. Twenty out of the retrieved 24 studies satisfied the inclusion criteria and were included in this systematic review and meta-analysis with a total sample size of 4070 participants that ranged from 30 patients [ 19 ] to 1463 patients [ 23 ]. Treatment outcomes in all studies were assessed using clinical and parasitological criteria according to WHO guidelines [ 10 – 12 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…were also included in this review. Twenty out of the retrieved 24 studies satisfied the inclusion criteria and were included in this systematic review and meta-analysis with a total sample size of 4070 participants that ranged from 30 patients [ 19 ] to 1463 patients [ 23 ]. Treatment outcomes in all studies were assessed using clinical and parasitological criteria according to WHO guidelines [ 10 – 12 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the double mutant genotype (51I/108N) was predominant from East African isolates than other areas because the majority of the isolates were from Sudan origin. The double mutation was prevalent in Sudan in 2007 [30] and still maintains the double mutant genotype with an emerging triple mutation [31]. Triple mutants (51I, 59R, 108N), which associated with highlevel pyrimethamine resistance [10,11], were almost fixed in the African population [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…In 2006, a study in the east of the country reported a day 28 PCR corrected efficacy of 93.5% for AS/SP for P. falciparum [ 31 ]. Other clinical studies conducted between 2010 and 2015 at six sites suggest that the PCR corrected efficacy of AS/SP against P. falciparum by day 28 generally exceeds 95%, except for one site in Gedaref, in the East of the country, where the efficacy fell from 91% in 2012 to 87% in 2015 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%